Detention of Refugees in New Zealand Law: Striking a Balance Between Refugee Rights and National Security - Frater, Charlotte (Victoria University of Wellington Law Review, 2003)
In this paper the author examines New Zealand’s international obligations regarding the detention of Refugees and how these are implemented domestically. Article 31 of the Refugee Convention 1951 states that their detention is only permissible where necessary, and related documents outline these circumstances. The Convention contains an appropriate balance between the special needs of refugees and respect for national security, which unfortunately is not always present in our domestic legislation. Section 128(5) of the Immigration Act 1987 allows refugees to be detained. However, this is subject to the requirements of the Convention due to section 129X(2) of the Act. The Court of Appeal in the Refugee Council case1 decided that an operational instruction issued after September 11, and coinciding with a significant increase in the numbers detained, was not unlawful. The author argues that the balance has swung too far in favour of national security, but concedes that the Immigration Amendment Act 2002 has gone some way to rectify the situation by providing conditional release procedures.